Hydration of oligo(ethylene glycol) self-assembled monolayers studied using polarization modulation infrared spectroscopy. - Skoda, M; Jacobs, R; Willis, J; Schreiber, F (2007)
The interaction with water of protein-resistant monolayers (SAMs), self-assembled from (triethylene glycol) terminated thiol HS(CH2)11(OCH2CH2)3OMe solutions, was studied using in and ex situ polarization-modulated Fourier transform infrared spectroscopy. In particular, shifts in the position of the characteristic C-O-C stretching vibration were observed after the monolayers had been exposed to water. The shift in frequency increased when the SAM was observed in direct contact with a thin layer of water. It was found that the magnitude of the shift also depended on the surface coverage of the SAM. These findings suggest a rather strong interaction of oligo(ethylene glycol) SAMs with water and indicate the penetration of water into the upper region of the monolayer.